PERSEPSI NETIZEN TERHADAP PEMANFAATAN APLIKASI INSTAGRAM SEBAGAI MEDIA DAKWAH STUDI AKUN INSTAGRAM @BASYASMAN - Rohmah, Hidayatur; Afida, Wafi Ratul; Faqih, Nur Abdullah; Azhimi Qalban, Anas (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
This research aims to investigate netizens' perceptions of the use of Instagram as a propaganda medium, with a focus on accounts@basyasman. Through qualitative field research methods and descriptive analysis, this research seeks to understand how netizens view the use of social media platforms, especially Instagram, in a religious context, as well as how they perceive their accounts.@basyasman as a preacher. Research data was collected through in-depth interviews, observation and documentation. Ten participants were selected to be interviewed in depth. The research results show that netizens have a positive perception of the account@basyasman. They appreciate Husain Basyasman's positive character and good personality, and recognize his strong intellectual and religious intelligence. Netizens also highlighted the way of preaching which is communicative and easy to understand by various groups, especially generation Z. Akun@basyasman managed to gain popularity and a large number of followers because of the impression he gave. His ability to convey religious messages that are relevant and attractive to young people has made him attractive to netizens. In this digital era, Instagram has become an effective platform in reaching a wider audience and providing a positive impact in spreading da'wah messages. This research provides valuable insights for the development of more effective da'wah strategies in the digital era. Understanding netizens' perceptions of the use of Instagram as a medium for preaching and account contribution@basyasman can help in designing content and strategies that are more relevant and attractive to the target audience, especially the younger generation.